Pericoronitis en terceros molares: Diagnóstico y tratamiento - Guaycha Torres, Daniela Cecivel (2022)
Pericoronitis is an infectious process characterized by inflammation of the percoronary sac that frequently occurs in semi-retained teeth. Currently, there are no specific data that mention a protocol for early diagnosis; it can even be confused with other pathologies due to the lack of knowledge of its clinical characteristics and its misdiagnosis. This bibliographic review is carried out to describe in depth the adequate diagnosis of pericoronitis, in addition to understanding the relationship of the third molars with this pathology; its clinical characteristics, and the appropriate treatment; which would lead to a better pre and postoperative control of pain, infection, and inflammation. For the present investigation, a non-experimental, descriptive, analytical, and retrospective study was carried out, including 26 scientific articles in English and Spanish and five theses obtained from the PubMed database, Ebscohost, Springer Open, Elsevier. From the analysis performed, 90% of the articles reviewed mention that the most common clinical features in third molars are: soft tissue inflammation, erythema, swelling, intense pain, halitosis, and limitation of oral opening. Therefore, 10% of the extraction of partially erupted third molars is due to the presence of pericoronitis due to the ease of food impaction between the tooth and the surrounding soft tissue, providing a favorable environment for the presence of microorganisms